Tetraaquatetrakis{μ(3)-3,3′-[(E,E)-ethane-1,2-diylbis(nitrilomethylidyne)]benzene-1,2-diolato}octazinc(II) N,N-dimethylformamide hexasolvate - Xu, Qin-Juan (International Union of Crystallography, 2009)
The asymmetric unit of the title compound [Zn(8)(C(16)H(12)N(2)O(4))(4)(H(2)O)(4)]·6C(3)H(7)NO, consists of eight Zn(II) cations, four tetravalent anionic ligands, L (4−) (L (4−) = 3,3′-(1E,1′E)-(ethane-1,2-diylbis(azan-1-yl-1-ylidene))bis(methan-1-yl-1-ylidene)dibenzene-1,2-bis(olate), four coordinated water molecules and six N,N-dimethylformamide solvate molecules. The coordination complex comprises an octanuclear Zn(II) unit with its Zn(II) centers coordinated in two discrete distorted square-pyramidal geometries. Four Zn(II) atoms each coordinate to two nitrogen atoms and two phenolate oxygen atoms from an individual L (4−) ligand and one coordinated water molecule. The other four Zn(II) atoms each bind to five phenolate oxygen atoms from three different L (4−) ligands. In the crystal structure, the Zn(II) complex unit, coordinated water molecules and dimethylformamide solvate molecules are linked via O—H⋯O and C—H⋯O hydrogen bonds. Molecules are connected by additional intermolecular O—H⋯O and C—H⋯O hydrogen bonds, forming an extensive three dimensional framework.